การตอบสนองของไม้ประดับ 4 ชนิด ต่อการให้แพกโคลบิวทราซอลในสภาวะขาดน้ำ - สุขเกลี้ยง ศศิธร; พิชกรรม ณัฏฐ; มีนะกนิษฐ อลิศรา; จารุวัฒนพันธ์ ทัศไนย (Thai Journal of Science and Technology, 2020)
The response of the 4 ornamental plants; i.e. Lantana montevidensis (Spreng.) Briq., Nephrolepis cordifolia (L.) C. Presl, Tradescantia spathacea Sw, and Wedelia trilobata (L.) Hitchc. on water-deficit condition after paclobutrazol application at concentrations of 0, 25, 50, 75 and 100 ppm was done to investigate the proper method for prolonging shelf life on landscaping plant material. The study was operated under the outdoor condition at the experimental field, Department of Horticulture, Faculty of Agriculture, Kasetsart University, Bangkok, during December 2018 to February 2019. Pot plants were acclimatized for 2 weeks prior 40 mL paclobutrazol solution was once soil drench to each pot at 0, 25, 50, 75 or 100 ppm. Daily irrigation was supplied for 7 weeks, afterward, the studied plants were subjected to water-deficit (stop irrigation). The result found that 25-100 ppm paclobutrazol applications unaffected on vegetative growth, shoot length, and diameter of canopy for 7 weeks. After water-deficit exposure, L. montevidensis, N. cordifolia, and T. spathacea responded to paclobutrazol applications at 50, 25 and 100 ppm, on leaf senescence via the delaying of leaf color loss. For W. Trilobata, leaves on the control plant had lower color intensity than that of paclobutrazol treated one. Thus, paclobutrazol application might delay leaf senescence on L. montevidensis, N. cordifolia, and T. spathacea.